Cyanotic Nephropathy in an Adult Patient with Eisenmenger Syndrome: A Case Report and Literature Review - Fanyou Zhu; Rui Wen; Xiangling Tan; Hongjun Nie; Jiali Li; Qi Wang; Jiao Qin (Karger Publishers, 2024)
Introduction: Cyanotic nephropathy, a rare disease characterized by proteinuria, decreased estimated glomerular filtration rate, thrombocytopenia, polycythemia, and hyperuricemia, may occasionally be secondary to cyanotic congenital heart disease (CHD). There are currently no detailed diagnostic criteria or treatments for cyanotic nephropathy, owing to its extremely low incidence. Eisenmenger syndrome (ES) was initially defined by Paul Wood in pathophysiologic terms as "pulmonary hypertension (PH) at the systemic level, caused by a high pulmonary vascular resistance, with a reversed or bidirectional shunt at the aorto-pulmonary, ventricular, or atrial level." It typically develops in the presence of large, unrepaired atrial or ventricular septal defects, arterial shunts, or complex forms of CHD and is the most severe hemodynamic phenotype of pulmonary arterial hypertension associated with CHD. This study aimed to outline the case of an ES patient who developed cyanotic nephropathy and successfully achieved clinical remission through primary disease treatment and symptomatic management. Overall, this case expands our understanding of cyanotic nephropathy and lays a theoretical reference for the treatment of ES. Case Presentation: A 33-year-old Chinese female attended the outpatient department with abnormal urine test results over the past two and a half years. Following a comprehensive medical history collection, she underwent the necessary tests. Cardiac color ultrasound displayed a significant widening of the pulmonary artery and PH (severe), as well as mild tricuspid regurgitation and patent ductus arteriosus. The results of the kidney biopsy, combined with clinical findings, suggested a high risk of polycythemia-related kidney disease. She was eventually diagnosed with cyanotic nephropathy and ES. Her symptoms were relieved following symptomatic treatment, such as the administration of ambrisentan, febuxostat, and home oxygen therapy. Her follow-up visit at 6 months demonstrated improvements in hyperuricemia and a significant increase in physical strength. Conclusion: Cyanotic nephropathy is a rare condition in adults. Kidney biopsy remains the gold standard of diagnosis for various nephropathies. Active treatment of CHD and alleviating hypoxia may be pivotal for the treatment of cyanotic nephropathy.